A general solid-state synthesis of chemically-doped fluorescent graphene quantum dots for bioimaging and optoelectronic applications1. Issue 22 (14th June 2015) - Ma, Chong-Bo; Zhu, Zhen-Tong; Wang, Hang-Xing; Huang, Xiao; Zhang, Xiao; Qi, Xiaoying; Zhang, Hao-Li; Zhu, Yihan; Deng, Xia; Peng, Yong; Han, Yu; Zhang, Hua
<x xml:space="preserve">Abstract</x> A facile general method for synthesizing doped and undoped graphene quantum dots is reported, which is based on solid reaction of simple organic precursors.